Facilitation of Quercus ilex in Mediterranean shrubland is explained by both direct and indirect interactions mediated by herbs - Cuesta, Bárbara; Villar-Salvador, Pedro; Puértolas, Jaime; Rey Benayas, José M.; Michalet, Richard (Journal of Ecology, 2010)
1. Competitive and facilitative interactions shape plant communities. Whereas a number of studies have addressed competition and direct facilitation among plants in dry ecosystems, indirect facilitation has received little attention. 2. We investigated the relative importance of direct and indirect facilitation by the nurse plant Retama sphaerocarpa on late-successional Quercus ilex seedlings mediated by herb suppression in a Mediterranean shrubland in 2006 and 2007. We also studied whether facilitation outcome depended on the size of the facilitated seedlings. 3. A field experiment was carried out to test the effect of (i) position of Q. ilex seedling with respect to shrub canopy (under shrubs or in gaps), (ii) herb competition (presence or absence), and (iii) seedling size. 2006 was an average rainfall year while 2007 had a much more humid spring and a dryer summer than 2006. 4. In both years, nurse shrubs reduced seedling mortality whereas herbs increased it. In the average rainfall year, seedling mortality under shrubs was unaffected by herbs whereas in gaps it was significantly higher in presence of herbs. This showed that the nurse shrub indirectly facilitated the seedlings by reducing the competitive capacity of herbs. Conversely, facilitation was predominately direct during the humid spring and dry summer year since herbs hindered seedling survival similarly under the nurse shrub and in gaps. The nurse shrub directly facilitated the seedlings by reducing seedling photoinhibition and water stress. 5. Improvement of environmental conditions by Retama benefited smaller seedlings but not larger seedlings since the nurse shrub reduced mortality of smaller seedlings relative to that in gaps, but this effect was not observed for larger seedlings. This indicates that individuals within a seedling population may not have the same response to facilitation. 6. Synthesis. Both indirect and direct facilitation are important mechanisms for Q. ilex regeneration in Retama shrubland and their importance seems to vary with climatic conditions. Indirect facilitation by release of herb competition under nurse shrubs is important in years of dry springs when competition between nurse shrubs and herbs is high, whereas direct facilitation mediated by microclimate amelioration increases with summer aridity.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: chlorophyll fluorescence; herb competition; Quercus ilex; retama sphaerocarpa; seedling size; water potential

Why do large, nitrogen rich seedlings better resist stressful transplanting conditions? A physiological analysis in two functionally contrasting Mediterranean forest species - Cuesta, Bárbara; Villar-Salvador, Pedro; Puértolas, Jaime; Jacobs, Douglass F.; Rey Benayas, José M. (Forest Ecology and Management, 2010)
We analysed the physiological bases that explain why large and high nitrogen (N) concentration seedlings frequently have improved survival and growth relative to small seedlings in Mediterranean woodland plantations. Large seedlings of Aleppo pine (Pinus halepensisMill.) and holm oak (Quercus ilex L.) with high N concentration (L+), and small seedlings with either high (S+) or low (S−) N concentration, were planted on two sites of different weed competition intensity that created contrasting stress conditions. Seedling survival, growth, gas exchange, N remobilization (NR) and uptake (NU), and water potential were assessed through the ﬁrst growing season. Weeds reduced survival and growth, but seedling response to weed competition varied among phenotypes and between species. At the end of the ﬁrst growing season, L+ Aleppo pine seedlings had higher survival than both small seedling types in presence of weeds but no differences were observed in absence of weeds. Mortality differences among phenotypes occurred in spring but not in summer. L+ Aleppo pines grew more than small Aleppo pines independently of weed competition. No holm oak seedling type survived in presence of weeds and no mortality differences among phenotypes where observed in absence of weeds, although L+ holm oak seedlings grew more than small seedlings. Mortality and growth differences in Aleppo pine were linked to marked physiological differences among phenotypes while physiological differences were small among holm oak phenotypes. L+ Aleppo pines had greater root growth, gas exchange, NR, and NU than small seedlings, irrespective of their N concentration. Seedling size in Aleppo pine had a greater role in the performance of transplanted seedlings than N concentration. The functional differences among oak phenotypes were small whereas they were large in pine seedlings, which led to smaller differences in transplanting performance in holm oak than in pine. This suggests that the nursery seedling quality improvement for planting in dry sites could depend on the species-speciﬁc phenotypic plasticity and functional strategy. Improved transplanting performance in large Aleppo pine seedlings relative to small seedlings was linked to greater gas exchange, root growth and N cycling.
Keywords: competition; Nitrogen remobilization; photosynthesis; Pinus halepensis; Quercus ilex; Root growth; Stomatal conductance; Survival; water potential